ON THE DISTRIBUTION TAIL OF A SUM OF RANDOM NUMBER OF INDEPENDENT RANDOM VARIABLES - Danielyan, I. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
Regular variation conditions for distribution tail of a sum of random number of independent random variables are established. It is assumed that the random index does not depend on the summands.
Keywords: random index; distribution tail of a sum of random number; random variables